DOI: 10.18174/423035
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid production in Aspergillus niger and other filamentous fungi

Abstract: Propositions1. Medium acidification is primarily a cause, rather than an effect, of Aspergillus niger citrate secretion.(this thesis) 2. A holistic systems biology approach should consider the organism in the context of its environment.(this thesis) 3. Metabolism has more than two spacial dimensions and should be studied as a system rather than a map.4. Cancer cells behave as a microorganism in a foreign environment.5. Referrals to authors rather than researchers highlights the skewed perception of scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 203 publications
(438 reference statements)
0
6
0
Order By: Relevance
“…Based on RNAseq data, comparing the growth and the citrate accumulation phase of the fermentation, Yin et al [ 42 ], reported a list of transporter genes up-regulated during the citrate production phase. This shortlist was proposed to contain candidate citrate transporters, but did not include the citT gene first discovered by Odoni et al [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on RNAseq data, comparing the growth and the citrate accumulation phase of the fermentation, Yin et al [ 42 ], reported a list of transporter genes up-regulated during the citrate production phase. This shortlist was proposed to contain candidate citrate transporters, but did not include the citT gene first discovered by Odoni et al [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The CitT exporter protein belongs to Major Facilitator Superfamily (MFS) [ 19 , 20 ]. From the 336 putative MFS encoding genes contained in the genome of A. niger N402, 78 and 87 of them were significantly up- and down-regulated in citrate condition compared to glucose (as reference), respectively ( Supplementary Data S1 in sheet N402_MFS online).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations